Efeitos moduladores do ácido ascórbico quando associado ao cloridrato de doxorrubicina em células somáticas de Drosophila melanogaster, tratadas na presença e ausência de luz - Fragiorge, Edson José (2000)
Doxorubicin (DXR), an anthracycline is a chemotherapeutic agent widely used as an antineoplastic agent. This drug and its metabolites have been shown to be stable at room temperature in the dark for at least 24 h, but are unstable when exposed to light. The clinical efficacy of DXR is compromised due to the production of free radicals, which leads to cardiac toxicity. The modulatory effects of vitamin C (ascorbic acid - AA), a free radical scavenger, against the direct genotoxicity of DXR were investigated by the Somatic Mutation And Recombination Test (SMART) in vivo. in Drosophila melanogaster. The following intersections were employed:1) Standard cross - ST in which females flr3 / In (3LR) TM3, ri pp sep 1 (3) 89Aa bx34e and BdS were crossed with males mwh / mwh; 2) High metabolic bioactivation capacity (High bioactivation crozz - HB) in which females ORR; flr3 / In (3LR) TM3, ri pp sep l (3) 89 Aa bx34e and BdS were crossed with mwh / mwh males. This latter crossing is characterized by a high sensitivity to promutagens and procarcinogens. Larvae resulting from these two crossings were simultaneously treated for approximately 48 h with DXR and AA, protected from light and exposed to ambient light. Negative and positive controls were included in both series of experiments. Emerging adult wings were analyzed for the occurrence of different types of mutant spots. Results from two separate studies are presented (1) When exposed to ambient light, ascorbic acid (50 and 100mM) had no genotoxic effects, while DXR (Adriamycin) (0.1 and 0.2 mg / ml distilled water). ) was clearly and equally genotoxic at both crosses. The addition of AA to the DXR-containing drosophila culture medium resulted in an inverse protective effect, as the lower dose of 50mM reduced the frequency of DXR-induced blemishes, while the 100mM dose had no effect, or increased the frequency. of spots from both intersections. (2) To determine the stability of DXR (Doxin), two batches of larvae emerging from both crosses were treated simultaneously for approximately 48 h with DXR and AA, protected from light and exposed to ambient light. The addition of AA to the DXR-containing Drosophila culture medium increased the frequencies of spots, demonstrating a dose-response effect in the ST series for both light-exposed and ambient-light-protected. However, an inverse protective effect was observed in the HB series, as the lower dose of 50 mM reduced the frequency of DXR-induced blemishes, while the 100mM dose had no effect (when exposed to light), or increased spots (when protected from light). These results suggest that a production of added AA may interfere with free radicals produced by DXR and other reactive metabolites, which increase stain frequencies.